2018
DOI: 10.1111/jmwh.12884
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes for the First Year of Ontario's Birth Center Demonstration Project

Abstract: IntroductionIn 2014, Ontario opened 2 stand‐alone midwifery‐led birth centers. Using mixed methods, we evaluated the first year of operations for quality and safety, client experience, and integration into the maternity care community. This article reports on our study of safety and quality of care.MethodsThis descriptive evaluation focused on women admitted to a birth center at the beginning of labor. For context, we matched this cohort (on a 1:4 basis) with similar low‐risk midwifery clients giving birth in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 24 publications
2
11
1
Order By: Relevance
“…Ontario has emerged as a leader in midwifery as it was the first province to regulate the profession, has the largest and most established workforce, and trains the most midwives in the country. Supportive evaluations from the first year of operations of the two birth centres have found that clients had significantly fewer interventions and care reflected current best practices [88]. The findings from the evaluation are consistent with research internationally and support the safety of midwife-led out-of-hospital births for low-risk populations [77][78][79]89].…”
Section: Discussionsupporting
confidence: 55%
“…Ontario has emerged as a leader in midwifery as it was the first province to regulate the profession, has the largest and most established workforce, and trains the most midwives in the country. Supportive evaluations from the first year of operations of the two birth centres have found that clients had significantly fewer interventions and care reflected current best practices [88]. The findings from the evaluation are consistent with research internationally and support the safety of midwife-led out-of-hospital births for low-risk populations [77][78][79]89].…”
Section: Discussionsupporting
confidence: 55%
“…In the first year of operations of the 2 birth centers, we observed a transfer rate of 26.3% (130 transfers out of 495 admissions), 18 which was higher than the transfer rate of our survey sample. It is unknown why the transfer rate of our survey sample is lower than the overall birth center–hospital transfer rate for the corresponding period.…”
Section: Discussioncontrasting
confidence: 81%
“…Although the self‐reported rates of assisted vaginal births and cesarean births were higher in the hospital group in our study, this could be due to underlying factors in self‐selection for a hospital birth. More discussion of these outcomes can be found in our previous work that included a matched control group 18 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations